2021
DOI: 10.1097/jcp.0000000000001513
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Breast Cancer With Prolactin Elevating Antipsychotic Drugs

Abstract: Purpose/Background: Antipsychotic drugs are well established to alter circulating prolactin levels by blocking dopamine D 2 receptors in the pituitary. Prolactin activates many genes important in the development of breast cancer. Prior studies have found an association with antipsychotic use and risk of breast cancer.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…Antipsychotics that act by antagonizing dopamine, thereby raising circulating PRL, promoted tumorigenesis in experimental models initiated by RCAS-caErbB2, RCAS-HrasQ61L and MMTV-Wnt-1 ( 97 ). A recent study found that patients using these drugs had a significantly increased risk of breast cancer ( 20 ). Together, these observations in patients and murine models indicate a role(s) for PRL in progression of early lesions.…”
Section: Prl Actions In Development Of Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Antipsychotics that act by antagonizing dopamine, thereby raising circulating PRL, promoted tumorigenesis in experimental models initiated by RCAS-caErbB2, RCAS-HrasQ61L and MMTV-Wnt-1 ( 97 ). A recent study found that patients using these drugs had a significantly increased risk of breast cancer ( 20 ). Together, these observations in patients and murine models indicate a role(s) for PRL in progression of early lesions.…”
Section: Prl Actions In Development Of Breast Cancermentioning
confidence: 99%
“…Pituitary PRL secretion is influenced by many factors, and circulating levels in nonpregnant women vary considerably ( 16 18 ). In addition to physiological stimuli, estrogen-progestin menopausal hormone therapy (MHT) raises circulating PRL ( 18 ), and anti-psychotics that antagonize dopamine induce hyperprolactinemia ( 19 , 20 ). Further, PRL also can be expressed by non-lactotrophs, including within the mammary gland ( 21 23 ), and by breast cancer cells themselves ( 24 – 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…All nine studies defined the outcome of interest as the first-time diagnosis of breast cancer, with five studies specifying the adopted diagnosis explicitly based on International Classification of Diseases (ICD) (Wang et al, 2002;Chou et al, 2017;Pottegård et al, 2018;Taipale et al, 2021;Rahman et al, 2022), one of which also identified first claims of breast cancer surgeries without an ICD code diagnosis as cases (Wang et al, 2002). Either surgery, chemotherapy or hospitalisation for breast cancer in addition to the diagnosis with ICD code was adopted for one study (Rahman et al, 2022) (Wang et al, 2002;Chou et al, 2017;Pottegård et al, 2018;Taipale et al, 2021;Rahman et al, 2022) that specified the diagnosis based on ICD codes supported the association. From the remaining studies that received quality assessment scores ranging from seven to nine stars (Mortensen, 1987;Dalton et al, 2006;Hippisley-Cox et al, 2007;Chou et al, 2017;George et al, 2020), both association and non-association were observed.…”
Section: Outcomebreast Cancermentioning
confidence: 99%
“…They reported HRs 2.49 (95% CI 1.69-3.66) and 1.05 (95% CI 0.58-1.87) for mean antipsychotic exposure of less than 28 and greater than 245 g/year, respectively. Some studies have also investigated the prolactin-elevating properties of antipsychotics and its association with breast cancer development (Chou et al, 2017;Pottegård et al, 2018;Taipale et al, 2021;Rahman et al, 2022). Exposure to antipsychotics with prolactin-elevating properties were included in Pottegård et al (2018), to which long-term exposure showed an increased risk of breast cancer.…”
Section: Exposureantipsychotic Usementioning
confidence: 99%
“…Furthermore, emerging evidence shows that prolactin has protumor properties in breast, prostate, colorectal, liver, ovarian, and endometrial cancers [14]. Recently, several epidemiological studies showed that prolactin-elevating antipsychotics increase the risk of breast cancer and breast cancer-specific mortality [15][16][17]. Therefore, more attention is needed to dissect the role of antipsychotics in cancer progression.…”
Section: Introductionmentioning
confidence: 99%